Application and Development of High Temperature Heat Pumps in China - 赵力 (Zhileng xuebao)
The situation is described about application and development of the high temperature heat pumps (HTHP) in China recently. Some engineering examples and systematic parameters of the HTHP are stated. Some published research conclusions of the HTHP are summarized, such as working fluids for the HTHP and parts matching. According to above information, some shortcomings of current studies are pointed out and the future directions of research and development are suggested.